The Case of Construction Industr An Evaluation of the Lending Model of Commercial Banks in South Africa: The Case of Construction Industry : An Evaluation of the Lending Model of Commercial Banks in South Africa: The Case of Construction Industry - Yolande Mtsweni, Lindy; Serumaga-Zake, Philip; Kruger, Jan (Advances in Social Sciences Research Journal, 2020)
The purpose of this study was to evaluate the commercial banks’ lending model for small businesses in South Africa. The multiple case study design and purposive sampling were used to select six small businesses from a bank’s database for the study. The qualitative data was categorised and analysed thematically. It was found that the lending criteria are based on the bank and client’s long-term relationship, client’s background, character, collateral, capital, capacity and affordability, that the lending model is helping to grow small businesses in the country. The commercial banks’ lending policy should allow flexibility, among others, in terms of the minimum deposits and interest rates charged.